Evaluation of Shampoo by Quality Control: Review - Arnita Annisanur; Ida Musfiroh (Universitas Padjadjaran (Unpad), 2022)
Shampoo is a product that is used to clean hair from dirts and also for specific therapeutic objectives such as conquering dandruff and hair loss. Product evaluation is a step that cannot be avoided to ensure product quality, including shampoo. As stated in the Good Manufacturing Practice guidelines, in the process of releasing product, the quality control in pharmaceutical industry must guarantee that the appropriate tests have been performed. The purpose of this review is to determine what attributes need to be evaluated in shampoo preparations. Datas for this review were obtained from national and international scientific publications published in the last 10 years using websites such as PubMed, Science Direct, and Springer. The keywords used in the search process are shampoo, evaluation of shampoo, types of shampoo. Final number of articles that used are 50 articles. Based on the search results, it is concluded that the evaluation of shampoo preparations consisted of testing physical appearance, homogeneity test, pH, solid content, viscosity, cleansing ability, and others. Keywords: Shampoo, quality control, products evaluation.